Respostas
respondido por:
5
a) f(1) = 2x -5
y= 2.1 -5
y= 2 -5
y= -3
b) f(0) = 2x-5
y= 2.0 -5
y= -5
c) f(-1) = 2x -5
y= 2. (-1) -5
y= -2 -5
y= -7
d) g(2)=-x+3
y= -2 +3
y= 1
e) g(-2)=-x+3
y= -(-2) +3
y= 2+3
y= 5
espero ter ajudado :)
y= 2.1 -5
y= 2 -5
y= -3
b) f(0) = 2x-5
y= 2.0 -5
y= -5
c) f(-1) = 2x -5
y= 2. (-1) -5
y= -2 -5
y= -7
d) g(2)=-x+3
y= -2 +3
y= 1
e) g(-2)=-x+3
y= -(-2) +3
y= 2+3
y= 5
espero ter ajudado :)
Anonimou:
Ajudou e muito!! obrigada linda
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás